A Dynamical Perspective of the Extreme Rainfall Event Over Eastern Northeast Brazil in May 2022 - Shunya Koseki; Isabelle Vilela; Doris Veleda (Meteorological Applications, 2025)
ABSTRACT This study investigated how the extreme rainfall event over eastern Northeast Brazil (ENEB), occurring at the end of May 2022, was induced dynamically using observational and reanalysis data. On a monthly time scale, a wet‐spell condition was found over the ENEB region in May 2022, indicated by enhanced onshore‐ward moisture flux and a widely spreading positive precipitation anomaly. At a shorter time scale, the ENEB region experienced continually intense rainy days from May 21st to 28th peaking on May 28th. Focusing on the most intense rainfall event on May 28th, a shallow vortex disturbance of a tropical easterly wave can be responsible for this intense event. This easterly wave is initiated over the south tropical Atlantic adjacent to the ENEB region, and we suggest that a strong zonal wind shear zone associated with a synoptic‐scale high‐pressure system generates the vortex as barotropic instability. Even though the vortex center did not make a landfall over the ENEB region, a part of the vortex band is elongated along the coastal line of the ENEB region and the vorticity and moisture flux convergence intensify drastically over the coastal ENEB region. Reinforced fluid deformation along the coastal line indicates the extension and intensification of the vortex band. The coastal enhancement of vorticity, convergence, and deformation can be interactive, and the sea‐land contrast may cause the enhancements due to surface condition change. This study provides a new dynamical insight into the intense precipitation over the ENEB region.